RANCANG BANGUN SISTEM PERPUSTAKAAN UNIVERSITAS TADULAKO MENGGUNAKAN RADIO FREQUENCY IDENTIFICATION DAN SENSOR PASSIVE INFRARED - Sani, Asrul; Nugraha, Deny Wiria; Hendra, Andi (-)
Radio frequency identification (RFID) is a tool for identifying objects using radio waves. RFID reader consists of a reader and a tag as the object is read. This technology is efficiently used in the manual library UNTAD as library card for its use without having direct contact (Contacless). Results of identification RFID reader in the form of a unique series of numbers. RFID reader is connected directly to a PC via a USB cable (Universal Serial Bus), so that the identification appear on the LCD monitor screen. The identification result is managed by the application that is made from Visual Basic 6 with GUI (grapichal User Interface) that simple connected in Acess 2007 database so that the library data is stored properly. Microcontroller ATMega8535 serves as a voice recorder module controller ISD 1820 remind visitors to fill out the list of visitors of the PIR sensor detection results when there are visitors who come in and as recipients visitor data contained in the application is then displayed on the LCD 2x16. From the combination of these technologies can overcome UNTAD library system is still manual because it produces a rapid and accurate data.